Mechanism of Immunoregulatory Properties of Vasoactive Intestinal Peptide in the K/BxN Mice Model of Autoimmune Arthritis - Leceta, Javier; Garin, Marina I.; Conde, Carmen (Frontiers in Immunology, 2021)
1 The K/BxN mouse model of rheumatoid arthritis (RA) closely resembles the human disease. Arthritis results from autoreactive KRN T cells recognizing the glycolytic enzyme glucose-6-phosphate isomerase (GPI) autoantigen that provide help to GPI-specific B cells resulting in the production of pathogenic anti-GPI antibodies that culminate in arthritis symptoms from 4 weeks of age. Vasoactive intestinal peptide (VIP) is a neuropeptide broadly distributed in the central and peripheral nervous system that is also expressed in lymphocytes and other immune cell types. VIP is a modulator of innate and adaptive immunity, showing anti-inflammatory and immunoregulatory properties. Basically, this neuropeptide promotes a shift in the Th1/Th2 balance and enhances de differentiation of T regulatory cells (Treg). It has demonstrated its therapeutic effects on the collagen induced arthritis (CIA) mouse model of RA. In this hypothesis and theory article we conclude that the immunoregulatory properties of VIP may be due to the inhibition of the T cell plasticity to nonclassic Th1 cells and the potentiation of follicular regulatory T cells (Tfr). The consequences of these regulatory properties are the reduction of systemic pathogenic antibody titers.